LAPORAN KEUANGAN SEBAGAI BENTUK TRANSPARANSI PENGELOLAAN ANGGARAN IPDN KAMPUS KALIMANTAN BARAT - wawan suwanda; Dety Pratiwi (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2018)
Budget User Proxy / Property User Proxy must compile and submit a Financial Report which includes Budget Realization Report, Balance Sheet, Operational report, report on changes in equity and Notes to Financial Statements in the context of preparing the Central Government Financial Report (LKPP). IPDN Finance Report West Kalimantan Campus The first semester of 2017 is a report covering all financial aspects managed by IPDN West Kalimantan Campus originating from APBN. Financial Reports of the IPDN Satker in West Kalimantan Semester I of the 2017 Fiscal Year have been prepared and presented in accordance with Government Regulation Number 71 of 2010 concerning Government Accounting Standards (SAP). The purpose of this study is to see how far the form of transparency conducted by IPDN West Kalimantan Campus in conducting budget management presented in the form of Financial Report.Keywords: Financial Report, Transparency and Budget.